Orbit properties of massive prolate galaxies in the Illustris simulation - Wang, Yougang; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We explore orbit properties of 35 prolate-triaxial galaxies selected from the Illustris cosmological hydrodynamic simulation. We present a detailed s